Hybrid Simulation of Turbulent Natural Convection in an Enclosure with Thermally-Conductive Walls; International Journal of Applied Mechanics; Vol. 13, iss. 6 - Nee A. E. Aleksandr Eduardovich (2021, 2021)
Title screen